The Barriers and Enablers of Primary Healthcare Service Transition From Government to Community Control in Yarrabah: A Grounded Theory Study - McCalman, Janya; Jongen, Crystal Sky; Campbell, Sandy; Fagan, Ruth; Pearson, Kingsley; Andrews, Suzanne (Frontiers in Public Health, 2021)
Abstract Introduction: Consistent with the aspirations of First Nations Australians for control over the provision of health services to their communities, 123/196 (63%) of Australia’s First Nations-specific primary health care services are community-controlled. Yet despite policy commitment over 30 years, the transition of government-run First Nations’ primary healthcare services to First Nations community control has been slow. This paper identifies the barriers and enablers to the transition from Queensland Health to Gurriny Yealamucka community-controlled health service of the delivery of primary healthcare services in Yarrabah. Methods: 14 Gurriny and Queensland Health (QH) personnel involved in the transition of primary healthcare services to community control in Yarrabah were interviewed. These transcripts and 88 Gurriny organisational documents were analysed using grounded theory methods. Results: Barriers and enablers to transition were identified at three levels: those internal factors within Gurriny, external factors directly related to the government handover, and broader structural and policy factors outside the control of either Gurriny or QH. Barriers at the Gurriny organisational level were an internal lack of experience and capacity, and varying levels of community confidence; enablers were leadership stability and capacity, community mandate, relationships with partner organisations, and ability to provide service continuity. Barriers in Gurriny’s relationship with QH were a lack of certainty, transparency and prioritisation of the transition process; systemic racism; difficulties obtaining and maintaining the necessary workforce; limited resources including insufficient, unstable and inappropriate funding support; and problems with information sharing; enablers were performance frameworks to keep transition progress on track. Barriers in broad policy environment were an unsupportive Queensland government policy environment; government bureaucracy; and delays, conflicts and divisions; enablers were high-level government support and commitment. Conclusions: The evaluation of Yarrabah’s transition process suggests that future such transitions will require planning and commitment to a long-term, multi-faceted and complex process, encompassing the required level of authorisation and resourcing. This case example of a transition from government to community control of PHC highlighted the ongoing power issues that are faced every day by community-controlled organisations that co-exist with mainstream health systems within a colonial power structure.